2013
DOI: 10.4103/0976-500x.107678
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid prevents progression of streptozotocin induced diabetic nephropathy and protects renal microstructures in Sprague Dawley rats

Abstract: Objective:To study the effect of oleanolic acid (OA) on streptozotocin induced diabetic nephropathy in Sprague Dawley rats.Materials and Methods:Four weeks after intra-peritoneal injection of streptozotocin (STZ; 55 mg/kg), the rats with proteinuria were grouped as: Control (non-diabetic, treated orally with vehicle), diabetic control (treated orally with vehicle) and three diabetic groups receiving 20, 40 and 60 mg/kg/day oral doses of OA. At the end of 8 weeks, urine and serum samples from the rats were proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…FBG, BUN, serum creatinine and urine microalbumin. [ 21 35 36 37 38 39 40 41 42 43 ] In our study, baseline FBG levels of the rats were found to be comparable across all the groups and were within the normal range. There was a dramatic rise in FBG after one week of STZ administration indicating successful induction of diabetes.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…FBG, BUN, serum creatinine and urine microalbumin. [ 21 35 36 37 38 39 40 41 42 43 ] In our study, baseline FBG levels of the rats were found to be comparable across all the groups and were within the normal range. There was a dramatic rise in FBG after one week of STZ administration indicating successful induction of diabetes.…”
Section: Discussionsupporting
confidence: 53%
“…Some researchers reported a decrease in weight, while others have reported an increase or no significant change in kidney weight. [ 33 34 35 ] In our study, kidney volume and weight were higher in the Enalapril group compared to the vehicle control group. However, there was no statistically significant difference in mean kidney weights among the different groups.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…This compound exhibited excellent inhibitory activities in vitro against α -amylase and lipase enzymes [ 117 ]. Recently, the effect of oleanolic acid on streptozotocin-induced diabetic neuropathy in Sprague Dawley rats has been studied [ 149 ]. The rats were divided into control group and diabetic group and were daily treated with 20, 40, and 60 mg/Kg doses of oleanolic acid up to four weeks.…”
Section: Pharmacologymentioning
confidence: 99%
“…In addition, OA was able to enhance the antioxidant function of mitochondria by increasing the expression of glutathione peroxidase 4 (Gpx4) and SOD [ 75 ]. Furthermore, OA was reported to improve the mitochondrial ultrastructure and function and antioxidant capacity by inhibiting MDA and ROS levels, as well as increasing CAT, SOD, and glutathione peroxidase (GSH-px) in diabetic rats [ 11 , 76 , 77 ].…”
Section: Anti-metabolic Syndromes’ Effectsmentioning
confidence: 99%